2014
DOI: 10.1002/path.4461
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory nerve: a shortcut for influenza and other viral diseases into the central nervous system

Abstract: The olfactory nerve consists mainly of olfactory receptor neurons and directly connects the nasal cavity with the central nervous system (CNS). Each olfactory receptor neuron projects a dendrite into the nasal cavity on the apical side, and on the basal side extends its axon through the cribriform plate into the olfactory bulb of the brain. Viruses that can use the olfactory nerve as a shortcut into the CNS include influenza A virus, herpesviruses, poliovirus, paramyxoviruses, vesicular stomatitis virus, rabie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
300
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(320 citation statements)
references
References 103 publications
7
300
0
13
Order By: Relevance
“…Such an intra-axonal migration pathway has long been known for neurotropic viruses such as rabies virus, herpesviruses, morbilliviruses, West Nile virus, and poliovirus (45)(46)(47), and also, the bacterium Burkholderia pseudomallei is suspected to migrate along cranial nerves (48). Although, once L. monocytogenes has entered the brain, the intrathecal immune response is intense and develops rapidly, L. monocytogenes is able to efficiently replicate and spread within the brain, causing a progressive and frequently fatal neurological disease (17,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an intra-axonal migration pathway has long been known for neurotropic viruses such as rabies virus, herpesviruses, morbilliviruses, West Nile virus, and poliovirus (45)(46)(47), and also, the bacterium Burkholderia pseudomallei is suspected to migrate along cranial nerves (48). Although, once L. monocytogenes has entered the brain, the intrathecal immune response is intense and develops rapidly, L. monocytogenes is able to efficiently replicate and spread within the brain, causing a progressive and frequently fatal neurological disease (17,29).…”
Section: Discussionmentioning
confidence: 99%
“…9). Transneuronal spread is a known pathway of intracerebral spread of rabies virus, measles virus, and herpesviruses and is a pathway suspected for many more viruses (47,(57)(58)(59). Proposed mechanisms include trans-synaptic transport, the establishment of microfusions, and non-trans-synaptic neuron-to-neuron transmission but remain to be elucidated for most of these viruses (47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, spread of influenza viruses to the brain usually occurs by the hematogenic route and also through the olfactory nerve. 27 Decreased replication in the brain in birds infected with Hp-NS230 or Hp-NSLp may be due to decreased tropism to endothelial cells; which is an important feature of HPAIV in domestic poultry. 28 These results indicated that NS1 can (1) modulate tropism to different tissues limiting systemic spread of the virus and (2) truncation is involved in this restriction but also other mutations in the NS1 play an additional role.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations have shown that neurons in the olfactory epithelium can be targeted by influenza A virus in mice (29), ferrets (24), and humans (40), and that H5N1 avian influenza strains in ferrets can spread along olfactory and trigeminal nerves to the OBs and brainstem after intranasal infection (24). In humans, influenza virus antigens in neurons and glia in the OBs and tracts, and the gyrus rectus have recently been found in an immune-compromised child (41).…”
Section: Influenza Virus Targets Olfactory Epithelium and Sleep-wakementioning
confidence: 99%
“…For example, a mutant of vesicular stomatitis virus can target DRN neurons and cause lifelong selective serotonin depletion in the brain (46). It is therefore possible that the several viruses that can invade the brain along the olfactory route (40,46), include mutant virus strains, which could more selectively target Orx/Hcrt neurons and cause lifelong sleep pattern changes in susceptible individuals.…”
Section: Influenza Virus Targets Olfactory Epithelium and Sleep-wakementioning
confidence: 99%